The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1161/01.cir.96.10.3633
|View full text |Cite
|
Sign up to set email alerts
|

Human Protein C Receptor Is Present Primarily on Endothelium of Large Blood Vessels

Abstract: These studies suggest that EPCR may be important in enhancing protein C activation on large vessels. The presence of high levels of EPCR on arterial vessels may help explain why partial protein C deficiency is a weak risk factor for arterial thrombosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
219
0
2

Year Published

1999
1999
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 270 publications
(228 citation statements)
references
References 32 publications
7
219
0
2
Order By: Relevance
“…Immunohistochemical studies revealed previously that EPCR expression is much greater on large vessel endothelium, particularly large arteries, and decreases until it is nearly undetectable in most capillary endothelial beds (9). The observation that protein C activation rates rise with increasing concentrations of EPCR provides the first evidence that there is an EPCR concentration dependence to protein C activation even when the EPCR concentration exceeds that of TM.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Immunohistochemical studies revealed previously that EPCR expression is much greater on large vessel endothelium, particularly large arteries, and decreases until it is nearly undetectable in most capillary endothelial beds (9). The observation that protein C activation rates rise with increasing concentrations of EPCR provides the first evidence that there is an EPCR concentration dependence to protein C activation even when the EPCR concentration exceeds that of TM.…”
Section: Discussionmentioning
confidence: 78%
“…EPCR expression varies throughout the vasculature (9) and is sensitive to a variety of effector systems (5). In vivo, EPCR expression levels are highest on the endothelium of large vessels, decreasing progressively with decreasing vessel size until the EPCR becomes undetectable by immunohistochemical approaches in most capillary beds (9,10). With cultured endothelium, EPCR expression is down-regulated by cytokines like tumor necrosis factor ␣ (5, 11).…”
mentioning
confidence: 99%
“…Each of these mediators is differentially expressed across the vascular tree (reviewed in Rosenberg andAird 1999 andAird 2001). For example, the endothelial protein C receptor is primarily expressed in large vessels (Laszik et al 1997), tissue factor pathway inhibitor in microvessels (Osterud et al 1995), and tissue-type plasminogen activator in pulmonary and cerebral arteries (Levin et al 2000). In response to systemic inflammation, the expression of these various procoagulants and anticoagulants changes in ways that differ between vascular beds.…”
Section: Endothelial Cell Phenotypesmentioning
confidence: 99%
“…EPCR, first cloned and characterized by the Esmon laboratory in the early 1990s, is primarily expressed by the vascular endothelium, preferentially on the endothelial cells of large blood vessels [5]. Recent studies have shown expression of EPCR in other cell types, including monocytes [6] and hematopoietic stem cells [7].…”
Section: Fviia Binding To Epcrmentioning
confidence: 99%